2013
DOI: 10.1111/jopy.12031
|View full text |Cite
|
Sign up to set email alerts
|

Conservatives Anticipate and Experience Stronger Emotional Reactions to Negative Outcomes

Abstract: The present work examined whether conservatives and liberals differ in their anticipation of their own emotional reactions to negative events. In two studies, participants imagined experiencing positive or negative outcomes in domains that do not directly concern politics. In Study 1, 190 American participants recruited online (64 male, Mage  = 32 years) anticipated their emotional responses to romantic relationship outcomes. In Study 2, 97 Canadian undergraduate students (26 male, Mage  = 21 years) reported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 49 publications
4
24
0
Order By: Relevance
“…Of the four that did, Cronbach’s alphas ranged from .53 to .71 for promotion scale and from .70 to .86 for the prevention scale. Consistent with the guiding hypothesis, Cronbach’s alpha was lowest for a sample with low literacy skills (Martinez et al, 2013) and highest for a highly educated sample (Worth et al, 2005) and another sample that was likely highly functioning because participants were recruited via mTurk and thus had access to computers and used the Internet (Joel et al, 2014). …”
Section: Methodsmentioning
confidence: 74%
“…Of the four that did, Cronbach’s alphas ranged from .53 to .71 for promotion scale and from .70 to .86 for the prevention scale. Consistent with the guiding hypothesis, Cronbach’s alpha was lowest for a sample with low literacy skills (Martinez et al, 2013) and highest for a highly educated sample (Worth et al, 2005) and another sample that was likely highly functioning because participants were recruited via mTurk and thus had access to computers and used the Internet (Joel et al, 2014). …”
Section: Methodsmentioning
confidence: 74%
“…Also, conservative participants reported that they did not know much (and did not want to know much) about the Ebola outbreak. The fact that conservatives tend to be more risk averse and have a stronger negativity bias than liberals might explain this finding (Hibbing, Smith, & Alford, ; Joel, Burton, & Plaks, ).…”
Section: Discussionmentioning
confidence: 99%
“…High conservatism is also related to greater skin conductance responses to aversive stimuli ( Oxley et al , 2008 ; Smith et al , 2011 ; Dodd et al , 2012 ), and increased levels of self-reported phobic-fears ( Hatemi et al , 2013 ). Furthermore, participants who are high in conservatism anticipate experiencing more negative emotional reactions when imagining a future negative event, and report experiencing a more negative emotional reaction toward receiving a lower than expected exam grade ( Joel et al , 2014 ). This study found that conservatism is associated with a greater increase in connectivity between the amygdala and BNST during conditions of unpredictable threat compared with safety.…”
Section: Discussionmentioning
confidence: 99%